Soil science and archaeology : three test cases from Minoan Crete - Morris, Michael (Prehistory monographs, 2002)
The environmental and cultural dynamics of Crete and the eastern Mediterranean -- Karphi. Sedimentation and pedogenesis -- Chrysokamino. An investigation of a vertisol in eastern Crete -- Vronda and Kastro at Kavousi. Deposition, erosion, and pedogenesis of alluvial and colluvial soils